The Influence of Learning Environment in Developing Students' Self-Regulated Learning Abilities in Higher Education - Friscilla Wulan Tersta; Hidayatul Arief; Refnida Refnida; Helty; Zenvi Ann M. Macalinao (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2025)
Self-regulated learning has been believed by several studies as one of the determinants of successful learning characterized by good academic performance. In fact, many learners are not able to regulate themselves optimally to stay motivated and consistent in learning. Therefore, this study aims to explore the influence of seven dimensions of learning environment on students' self-regulated learning. A cross-sectional research design was used in this study. Data were obtained from 419 4th semester students using a questionnaire packaged in the form of googleform. Data analysis in this study used Structural Equation Modeling Partial Least Squares (SEM-PLS). The findings in this study are involvement, investigation, task orientation, cooperation and equity have little effect on students' self-regulated learning. Meanwhile, lecture support and student cohesiveness proved to have no influence. Therefore, a learning environment that is able to create involvement, investigation, task orientation, cooperation and equity in the classroom learning process plays an important role in developing students' self-regulated learning ability.  These findings certainly provide a strong empirical basis for educational institutions to design appropriate interventions, develop relevant curricula, and create a conducive academic atmosphere to equip students with essential skills as adaptive lifelong learners who are ready to face global challenges.